Coeliac disease and collagenous colitis. Issue 773 (March 1990) - O'Mahony, S.; Nawroz, I. M.; Ferguson, A.
Abstract : We describe a case of collagenous colitis in a young man with coeliac disease who had responded clinically and histologically to a gluten-free diet three years previously. The collagenous colitis responded initially to oral corticosteroid therapy and he is now asymptomatic (and with normal rectal mucosa) on oral mesalazine. Collagenous colitis should be considered in the coeliac patient with diarrhoea despite adherence to a gluten-free diet.